Analise da estrutura e das propriedades elétricas de cu2 tise2 e cu3 feti2se4 - Gardes, Bernard (Semina: Ciências Agrárias, 1983)
Presentation of a hypothesis connecting the conductive behaviour of Cu2TlSe2 and semiconductive behavior of Cu3FeT12Se4 with the structural differences existings between these two compounds.